Growth analysis in seven potato varieties (Solanum tuberosum L.). - Borrego, Fernando (2006)
Seven potato (Solanum tuberosum L.) genotypes were evaluated, Norteña, Gigant, Mondial, Snowden, Alpha, Atlantic and Russett Burbank, under growth analysis efficiency and productivity criteria (six samples, every 18 days) like crop growth rate (CGR), Relative Growth Rate (RGR), Relative Leaf Growth Rate (RLGR), Leaf Area Ratio (LAR), Leaf Area Index (LAI) and Net Assimilation Rate (NAR). Differences were found (p £ 0.01) for variables in study (except for NAR), for sample variation differences (six along the cycle) being higher CGR in forth sample with Norteña and Russett Burbank genotypes. Norteña, Russett Burbank and Alpha were higher on TCR, showing a considerable increment on fifth and sixth sample. The best genotype on LAR were Atlantic and Snowden, showing Russett Burbank a pronounce decrement on fifth and sixth sample, because of foliar senescence. Respect to LAI, the best genotypes were Norteña and Gigant, being higher on forth and sixth sample, without senescence until this sample. For NAR, no differences were found between genotypes, Norteña was a little bit higher, showing the other five genotypes a similar behavior.